Análise de curvas de retenção e distribuição de poros de um latossolo vermelho distrofico submetido aos sistemas de plantio convencional e direto - Borkowski, Angelo Kuhn (2009)
To evaluate the environmental impacts generated by the tillage systems, it is necessary to evaluate the variations caused by them in the soil structure. The space porous is the best indicator of the soil structural quality, because it is responsible, among many factors, for transport phenomena of water and solutes in his interior and water retention. Tillage systems used in the soil tend to modify her structure. Thick way, the conventional tillage is characterized by the soil revolviment and mixture of the remains of the previous culture in their more interior layers. Already the no-tillage has for main characteristic the non revolviment of the soil, and the remains of the previous culture are left in the surface of the soil for incorporation of this material. The objective of this work was the survey of retention curve (RC), the which was determinate using the potential of 10,30,40, 60,80,100,300, 500,1000,4000,8000 cm de H2O, this dates when interpolates through of function of kind “spline cubic” allowed the construction of retention curves more detailed of that the curves obtained by traditional methods, so then, obtain of pores distribution curves (CDP) of a Red Dystrophic Latossoil under no-tillage and conventional tillage systems, in depths of until 0-40 cm. With base in those CDPs and in CRs to compare the modifications produced in the structure of this soil due to those two tillage types. Also, to study those modifications such complementally studies they were accomplished as: the analysis textural (mechanics) of the soil, the determination of his/her density and the determination of the macro, micro and total porosity of the soil. The results of this work showed that the soil under the system of no-tillage presented smaller density values in comparison with the soil under conventional tillage, values, respectively, of 1,09 against 1,20Mg/m3 (on average). Also, in the soil under conventional tillage an increase of 12% was observed in the density of the deepest layers (below 10cm) in comparison with the superficial layer (up to 10cm). That is an indicative of compacting of the soil, which, in general, it is attributed to the most intensive job of agricultural machinery in this type of tillage system. Already the soil under no-tillage presented a compressed layer, between 10 and 20 cm, with density approximately 8% larger than the adjacent layers, which was associated to traces of other tillage systems previously accomplished in the area under no-tillage. The results also indicated larger values of the total porosity and macroporosity for the soil under notillage. The retention curves CRs and of pores distribution CDPs showed larger homogeneity of the soil under no-tillage when compared to the soil under the conventional tillage. Except for the superficial layer (0-10 cm) of the soil under conventional tillage, CDPs showed that the distribution of sizes of pores of the soil under the direct and conventional plantings is trimodal with picks in the areas of rays among: 1 and 6μm; 9 and 25μm and 25 and 100μm. For the superficial layer of the soil under conventional tillage, CR and CDP indicated that the system of conventional tillage promotes a great desestructuration of the porous system of the soil, turning it less capable of keeping the water in his interior due to an enlargement of the distribution of pores above 25μm (macroporous).